Agreement of measurements of Transverse Cerebellar Diameter, Femur Length and Biparietal Diameter in sonographic determining of Gestational Age of fetuses with Intrauterine Growth Restriction - Nazanin Farshchian; Mohammad Gharib Salehi; Nasim Rashidi; Parisa Bahrami Kamangar (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: In human, the growth of the cerebellum may be less affected by Intrauterine Growth Restriction (IUGR). Then, measurement of transverse cerebellar diameter can be used as an appropriate measurement for determining the gestational age of fetus with IUGR. This study was performed with aim to evaluate the agreement of different biometric parameters such as transverse cerebellar diameter, femur length and biparietal diameter in sonographic determining of gestational age of fetuses with IUGR and comparing them. Methods: This cross sectional study was performed on 35 pregnant women with small abdomen suspected to IUGR fetuses who referred to sonography ward of Kermanshah Imam Reza Hospital in 2016. Gestational age was determined based on the LMP of patient. Ultrasound was performed for patients; gestational age was measured by Transverse Cerebellar Diameter (TCD) and other sonographic routine parameters, and then the results were compared. Data were analyzed by SPSS software (version 22) and paired t-test, Wilcoxon, Pearson and Spearman correlation coefficient. PResults: There was no significant difference between gestational age predicted by TCD parameter and LMP (P>0.05). But, gestational age determined by the parameters of BPD and Femur Length was significantly lower than gestational age based on LMP (P<0.05). Also, gestational age determined by TCD was significantly more than gestational age based on BPD and FL (P<0.05). Conclusion: Using Transverse cerebellar diameter parameters (TCD) to estimate the accurate gestational age of fetuses with intrauterine growth restriction can be safe and reliable.